2013
DOI: 10.1002/bsl.2088
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Brain Injury: Guidance in a Forensic Context from Outcome, Dose–Response, and Response Bias Research

Abstract: Traumatic brain injury (TBI) occurs at a high incidence, involving millions of individuals in the U.S. alone. Related to this, there are large numbers of litigants and claimants who are referred annually for forensic evaluation. In formulating opinions regarding claimed injuries, the present review advises experts to rely on two sets of information: TBI outcome and neuropsychological dose-response studies of non-litigants and non-claimants, and response bias literature that has demonstrated the relatively high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 120 publications
(137 reference statements)
0
10
0
Order By: Relevance
“…Typically, neuropsychological evaluation is used to characterize the level and pattern of cognitive impairment for those who have sustained a TBI (Finnanger et al., ; Hellawell, Taylor, & Pentland, ; Satz et al., ). TBI is often the result of accidents that may involve litigation or secondary gain (Sweet, Goldman, & Guidotti Breting, ). These factors have been shown to influence the validity of one's performance on neuropsychological tests (Gouse, Thomas, & Solms, ).…”
Section: Introductionmentioning
confidence: 99%
“…Typically, neuropsychological evaluation is used to characterize the level and pattern of cognitive impairment for those who have sustained a TBI (Finnanger et al., ; Hellawell, Taylor, & Pentland, ; Satz et al., ). TBI is often the result of accidents that may involve litigation or secondary gain (Sweet, Goldman, & Guidotti Breting, ). These factors have been shown to influence the validity of one's performance on neuropsychological tests (Gouse, Thomas, & Solms, ).…”
Section: Introductionmentioning
confidence: 99%
“…
Figure 3. This illustration is from Suchy et al [ 66 ] and demonstrates the dose–response relationship frequently reported between increasingly lower SVT performance and actual neuropsychological test findings [ 3 ]. Mean composite WMS-III T-score for individuals in the four groups were calclated: Valid = patients who produced above cut-score SVT performance during initial administration; Improvers = patients who initially produced non-valid SVT performance, but the repeat administration after confrontation yielded valid results; Non-improvers = patients who produced non-valid SVT performance initially and again after confrontation; N-CONF = patients who initially produced non-valid VSVT performance but were not confronted.
…”
Section: What Modifies Svt and Neuropsychological Test Performance?mentioning
confidence: 84%
“…Figure 3 shows this comparison. First, what is evident in viewing this figure is the so-called dose–response relation between level of SVT performance and neuropsychological test performance, in this case WMS-III performance [ 3 ]. Passing on the first SVT administration resulted in the highest performance, with below cut-point performance related to lower WMS-III performance.…”
Section: What Modifies Svt and Neuropsychological Test Performance?mentioning
confidence: 99%
See 1 more Smart Citation
“…3 is whether the Bfailed^SVT/PVT performance has any bearing on the neuropsychological test results and should they be interpreted? Incontrovertible findings at a group level consistently show significantly reduced neuropsychological test results in the group that Bfails^the SVT/PVT measure(s) compared to the Bpass^group even controlling for other demographic and disease/injury variables (Sollman and Berry 2011;Sweet et al 2013). While group data may be informative, the real issue for the clinician is what decisions to make with the individual case.…”
Section: The Modelmentioning
confidence: 92%